WATER MANAGEMENT OF RIVER ESTUARY FOR THE PREPARATION OF ECOTOURISM IN COASTAL AREA OF BALI PROVINCE - I Gst Agung Putu Eryani; I Ketut Irianto (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
Surface water flowing in the river is a resource of useful raw water to meet the needs of society and as irrigation water is managed by Subak in Bali, Indonesia. Bali has experienced water deficit, along with the increasing number of inhabitants and tourism activities. Results of research of the Ministry of Environment (MOE, 2009) stated that Bali has experienced water deficit of 7.5 billion m3/year in 2000 and 2015 deficit is estimated at as much as 27.6 billion m3 of water/year. The purpose of this research was to evaluate the potential of water in the estuary Saba in order to support ecotourism in coastal areas of the province of Bali and formulating water resource management scheme for coastal areas in Buleleng regency. This research uses quantitative methods with the research location is in the Saba river estuary in Buleleng Regency. Data collected consist of primary data and secondary data. Simulation models for water resources management and statistical analysis using software RIBASIM (River Basin Simulation). As a result of this research is the potential of water in the estuary Saba. The result of measurements in the dry season (September 2013) is amounted to 0.156 m3/sec and in the rainy season (January 2014) of 1,023 m3/sec. Potential water in Saba river estuary based on the simulation of RIBASIM is 9.34 million m3/year, can be used as society water domestic for 81 851 inhabitants, for the water industry (hotel) is 1364 rooms, amounted to 2 ha of fish pond water and for irrigation water (agricultural) is 148 ha. Results of water quality research to the smell, color, temperature, turbidity meet quality standards, while taste, and salinity do not meet quality standards. For the chemical aspect, that is pH and detergent meet quality standards while for BOD and COD does not meet the water quality standard Class I. In terms of biology, total coliform does not meet the quality standards of class I. Saba River water potential for ground water of 7.46 million m3 (6%), residual water irrigation (Return Flow) amounted to 54.74 million m3 (41%) and the balance/allocation of water in an area (water District) amounted to 71.54 million m3 (53%). Water resources management in the Saba River estuary for the water potential in the river estuary can be managed by making reservoirs (reservoir), and dam movement and arrangement of the beach.